The dynamics of job creation and job destruction: is sub-saharan Africa different? - Admasu Shiferaw; Arjun S. Bedi (Institute for the Study of Labor (IZA), 2009)
This paper analyzes the creation, destruction and reallocation of jobs in order to understand the micro-dynamics of aggregate employment change in African manufacturing. The nature and magnitude of gross job flows are examined using a unique panel data of Ethiopian manufacturing establishments over the period 1996-2007. We also assess the relative importance of firm demographics, industry effects and business cycles for job flows. The rates and patterns of job creation and destruction in our sample are comparable to the findings from developed and emerging economies suggesting that African firms adjust their labor force in a manner broadly similar to firms elsewhere and that African labor markets are not uniquely restrictive in terms of undermining job reallocation across firms. We also find, as in many other countries, that job reallocation is relatively higher in industries dominated by smaller and younger establishments. However, unlike other regions, job reallocation in our sample is pro-cyclical and its variation across industries bears little similarity to the patterns found in other developed and emerging economies. Small firms in Africa create jobs mainly at the point of market-entry and play a limited role in terms of contributing to manufacturing employment through post-entry expansion.
Keywords: J20; J23; J49; 330; Job creation; job destruction; job reallocation; firm dynamics; Sub-Saharan Africa; Ethiopia; Arbeitsmarkt; Industrielle Beschäftigung; Arbeitsmobilität; Arbeitsnachfrage; Unternehmensentwicklung; Beschäftigungseffekt; Äthiopien; Afrika südlich der Sahara